2013
DOI: 10.4049/jimmunol.1201897
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo Ablation of Plasmacytoid Dendritic Cells Inhibits Autoimmunity through Expansion of Myeloid-Derived Suppressor Cells

Abstract: Autoimmunity ensues upon breakdown of tolerance mechanism and priming of self-reactive T cells. Plasmacytoid dendritic cells (pDCs) constitute a unique cell subset that participates in the activation of autoreactive T cells but also has been shown to be critically involved in the induction of self-tolerance. However, their functional importance during the priming phase of an organ-specific autoimmune response remains unclear. In this study, we demonstrate that absence of pDCs during myelin antigenic challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 54 publications
3
22
0
1
Order By: Relevance
“…Increasingly, however, it is appreciated that deficient MDSC induction may play a role in autoimmunity 71,72. Induction of MDSCs can inhibit autoimmunity, most likely by interacting and suppressing T-cell effector responses 73,74. Notably, this is highly consistent with the studies by Ghazarian et al75 who showed that while Coxsackievirus B4 virus can accelerate T1D, natural killer T cell induced MDSCs that infiltrated into the islet, downregulated effector T cells, and prevented T1D.…”
Section: Novel Approaches To Immunotherapy For T1d: Targeting Innate supporting
confidence: 70%
“…Increasingly, however, it is appreciated that deficient MDSC induction may play a role in autoimmunity 71,72. Induction of MDSCs can inhibit autoimmunity, most likely by interacting and suppressing T-cell effector responses 73,74. Notably, this is highly consistent with the studies by Ghazarian et al75 who showed that while Coxsackievirus B4 virus can accelerate T1D, natural killer T cell induced MDSCs that infiltrated into the islet, downregulated effector T cells, and prevented T1D.…”
Section: Novel Approaches To Immunotherapy For T1d: Targeting Innate supporting
confidence: 70%
“…A reciprocal relationship has been shown to exist between pDCs and myeloid-derived suppressor cells (MDSC) (25). Because pDCs appear to be significantly elevated in the absence of galectin-3, we determined if there was a corresponding decrease in the number of immature myeloid cells, which have the potential to develop into MDSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, BTZ protection was lost in Ido1 −/− NOD mice (Figure 4B). In vivo depletion of pDCs (23) occurring at the time of BTZ administration negated the protective effect of the proteasomal inhibitor against diabetes development (Figure 4C), whereas depletion of pDCs occurring before BTZ treatment would not ablate its anti-diabetic effect (data not shown). Of interest, administration of anti-PDCA1 in the absence of BTZ also significantly reduced the percentage of animals that developed diabetes over time (Figure 4D).…”
Section: Resultsmentioning
confidence: 91%